ICap: Instrumented assessment of physical capability. Issue 1 (September 2015) - Godfrey, A.; Lara, J.; Del Din, S.; Hickey, A.; Munro, C.A.; Wiuff, C.; Chowdhury, S.A.; Mathers, J.C.; Rochester, L.
Highlights Instrumented testing of five physical capability tasks with a single accelerometer. Evaluated on a large cohort of older adults. iCap provides robust quantitative data about physical capability. iCap captures gait and postural control data known as sensitive to ageing/pathology. Methodology may have practical utility in a wide range of surveys and studies.